PROBLEMATIKA GURU DALAM MENGGUNAKAN MEDIA PEMBELAJARAN PADA KURIKULUM 2013 (STUDI KASUS DI SD NEGERI 1 TAMAN AYU) - Titin Nur Adianti; Muhammad Irawan Zain; Lalu Hamdian Affandi (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2021)
The purpose of this study is to describe the problem of teachers in using learning media in the 2013 curriculum at SDN 1 Taman Ayu, Gerung District. The research approach used is qualitative research with the type of case study research. Data collection techniques using interviews, observation and documentation. Data analysis used Milles and Huberman model data analysis. The results of the study indicate that the difficulties experienced by teachers include; 1) the difficulty of the teacher in choosing the media to be used. 2) Difficulties of teachers in using learning media 3) Difficulties of teachers in evaluating the use of learning media. the way the teacher overcomes these obstacles is to carry out reflection activities to restore student learning concentration, use student books, provide special guidance for students who have difficulties in understanding learning materials, evaluate media at other times. It can be concluded that teachers at SDN 1 Taman Ayu, Gerung Sub-district experienced problems in using learning media in the 2013 curriculum.